Eksploratori Skala Body Acceptance by Others-2 (Baos-2) Versi Bahasa Indonesia - Harta Prima Meza; Syifa Aryani; Devi Lusiria (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to conduct a linguistic and cultural adaptation of the Body Acceptance by Others Scale-2 (BAOS-2) into Indonesian and to evaluate its validity and reliability through an Exploratory Factor Analysis (EFA) approach. Participants consisted of 305 individuals aged over 17 years, selected using purposive sampling. The data suitability test showed a Kaiser-Meyer-Olkin (KMO) value of 0.932 and a significant Bartlett’s Test (p < .001), indicating that the data were appropriate for further analysis. The EFA identified a single main factor with an eigenvalue of 6.556, explaining 46.3% of the total variance, with all items having factor loadings ≥ 0.60. These findings indicate that the Indonesian version of the BAOS-2 has a stable unidimensional structure and excellent psychometric properties. The scale is culturally relevant and can be used to measure individuals’ perceptions of body acceptance by others in the Indonesian societal context. Furthermore, the reliability analysis showed that the instrument demonstrated good internal consistency, with a Cronbach’s Alpha value of 0.783, exceeding the minimum threshold of 0.70 and supporting the feasibility of using the scale in the Indonesian cultural context.